2020
DOI: 10.1108/ijoes-03-2019-0061
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of workplace spirituality on nurse work engagement: an empirical study on Indonesian government hospitals

Abstract: Purpose Highlighting the prominence of spirituality at work, this paper aims to scrutinize the mediating role of perceived person-organization fit (P-O fit) on the relationship between workplace spirituality and nurse work engagement in the context of two Indonesian government hospital. Design/methodology/approach Cross-sectional survey data of 138 nursing staff from two government hospitals operating in Indonesia were analyzed using structural equation modeling to estimate the mediation effects of perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 89 publications
2
22
1
2
Order By: Relevance
“…The potential explanation of this result is that, when people find their work to be meaningful, they feel inspired by, enthusiastic about, and dedicated to their work. This conclusion is steady with the previous study and extends the findings of Iqbal et al (2020), Petchsawang andMcLean (2017) andDe Carlo et al (2020) who proves that spirituality at work enhanced work engagement. Furthermore, our outcomes revealed that cancer survivor who is contemplated higher level on purpose or spiritual sense in their work are likely to expend more energy on work-related tasks.…”
Section: Discussionsupporting
confidence: 91%
“…The potential explanation of this result is that, when people find their work to be meaningful, they feel inspired by, enthusiastic about, and dedicated to their work. This conclusion is steady with the previous study and extends the findings of Iqbal et al (2020), Petchsawang andMcLean (2017) andDe Carlo et al (2020) who proves that spirituality at work enhanced work engagement. Furthermore, our outcomes revealed that cancer survivor who is contemplated higher level on purpose or spiritual sense in their work are likely to expend more energy on work-related tasks.…”
Section: Discussionsupporting
confidence: 91%
“…The finding suggests that the hospital's spiritual climate was the only significant predictor of the nurses' dedication and was a strong predictor on the regression model for vigour and absorption. This finding supports previous studies that reported how spirituality influences the work engagement of employees (Iqbal, Adawiyah, Suroso, & Wihuda, 2020;Roof, 2015). Roof (2015) reported a relationship between individual spirituality and work engagement of adult employees working in various industries in North…”
Section: Factors Influencing Nurses' Vigour Dedication and Absorptionsupporting
confidence: 90%
“…spiritual climate gained importance in a work environment (Iqbal, Adawiyah, Suroso, & Wihuda, 2020).…”
mentioning
confidence: 99%
“…Shehata also discovered that older nurses have more experience in providing nursing care to patients with serious illness. In addition, they had more confidence in pursuing and enforcing nursing care standards (35).…”
Section: Discussionmentioning
confidence: 99%